Hubungan Antara Kualitas Nyeri Dengan Kemampuan Aktivitas Fungsional Penderita Osteoartritis Lutut - Kurniawan, Fajar, Agus Widodo, S.Fis, M.Fis, Umi Budi Rahayu, S.Fis, M.Kes (2015)
Background: Osteoarthritis also called degenerative joint disease is an abnormality on cartilage (joint cartilage) is characterized by changes inclinical, histologist, and radiology. Namely the ability offunctional activity of the patient's ability to perform daily activities, limitations on patient activity due to the pain. Objective:To determine the relationship between the quality of pain with functional activity capability knee osteoarthritis sufferers. Methods: This study used epidemiological study design cross sectional analytic approach to determine the relationship between the quality of pain with the ability of functional activity. The number of samples was 34 respondents knee osteoarthritis who meet inclusion and exclusion criteria, obtained from non-random sampling with purposive random sampling technique. Data obtained from the questionnaires Visual Analogue Scale (VAS) and the Western Ontario and McMaster Universities OsteoarthritisIndex (WOMAC). Results: To test the hypothes isused Spearman test. Obtained strong correlation values between variables (r =0.510) and asignificant value of 0.002 (p <0.05). Conclusion: There is a relationship between the quality of pain with the ability of the functional activity of patients with osteoarthritis of the knee, that is, if an increase in the value of the quality ofthe pain will be followed by an increase in daily activities disabilities.